Evaluation of the anticoagulant effect and timing of the concomitant use of S-1 and warfarin. (October 2016) - Suzuki, Shinya; Ikegawa, Kiwako; Yamamoto, Kaori; Saito, Shinichiro
Objectives: To evaluate the effects of the timing of warfarin (WF) administration in patients with gastric cancer who received S-1 oral chemotherapy. Methods: This retrospective chart review collected patient data including the prothrombin time international normalized ratio (PT-INR). Patients were categorized into three groups based on the timing of WF administration in relation to S-1 oral chemotherapy: group A patients received WF before S-1 chemotherapy; group B patients started WF during S-1 chemotherapy; and group C patients started WF after completing S-1 chemotherapy. Results: A total of 21 patients with gastric cancer were included in the study; group A ( n  = 8), group B ( n  = 10) and group C ( n  = 3). Seven patients (88%) in group A, seven (70%) in group B and all of the patients (100%) in group C had >2.5 PT-INR. There was no significant difference in the time-to-exceed 2.5 PT-INR between groups A and B. Conclusions: These findings suggest that the timing of WF use in relation to S-1 chemotherapy might not be an important factor for PT-INR, although the low patient numbers included in the study should be taken into consideration.